Modeling buffered Ca2+ diffusion in a single human B cell: the role of endogenous Ca2+ buffer sand Ca2+ extrusion mechanisms - Félix-Martínez, G. J.; Godínez-Fernández, J. R. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2017)
In this paper, a model of the electrical activity of the human cell B-Cell was used in conjunction with a reaction-diffusion model of Ca2+ in order to analyze the spatiotemporal distribution of Ca2+ influx and extortion mechanisms, as well as a two endogenous buffer systems with difference kinetic characteristics. The effect of buffering and clearance of Ca2+ on the time course of the Ca2+ signal driven by spiking electrical activity was addressed.